Hepatoprotective activity of aqueous methanolic extract of Morus nigra against paracetamol-induced hepatotoxicity in mice (Bangladesh Journal of Pharmacology, 2014)
Morus nigra (Family Moraceae) is traditionally used injaundice, diabetes, hypertension, cough, fever and cancer. The current study was conducted to determine hepatoprotective activity of aqueous methanolic extract of leaves of M. nigra. Two doses of 250 mg/kg p.o and 500 mg/kg p.o showed that extract of M. nigra produced significant (p